TINJAUAN MASLAHAH TERHADAP KEBERADAAN DESTINASI WISATA BUKIT JADDIH BANGKALAN MENURUT PREKSPEKTIF MAQASID SYARIAH - ikrom, Moh Ikromul Ghoits (Qawwam : The Leader's Writing, 2022)
Jaddih Limestone Hill is a tourist destination which is a sculpture from limestone excavation, this excavation has a bad impact on the environment, but on the other hand this sculpture has become a special attraction that can generate money, currently excavation is still being carried out so that it creates Jaddih limestone hill tour. This study examines how the maslahah side takes into account the five objectives of the Shari'a, which can also be called the maqasid sharia elements, including hifzu din, hifzu nafs, hifsu aql, hifzu nasl, hifzu mal.